Bewertung des Sprödbruchwiderstands höchstfester Stähle im Mobilkranbau. Issue 3 (15th December 2021) - Kern, Andreas; Kirschbaum, Markus; Kucharczyk, Pawel; Langenberg, Peter; Schnitter, Frederik
Abstract: Die Festlegung von Zähigkeitsanforderungen für tragende Stahlstrukturen für Mobilkrane basiert bis heute größtenteils auf Erfahrungswerten oder deren Herleitung ist nicht transparent und nachvollziehbar. Mit bruchmechanischen Methoden konnten erstmals die Anforderungen an die Werkstoffzähigkeit für ein sprödbruchsicheres Betreiben differenziert bewertet und nachvollziehbar quantifiziert werden. Die vorgestellte Methodik lässt für verschiedene Bauteile, Beanspruchungsbedingungen und Vorgaben für Schweißnahtunregelmäßigkeiten die zu erwartende Lebensdauer sowie die erforderliche Werkstoffzähigkeit abschätzen. Abstract: Brittle fracture resistance of high‐strength steels in mobile crane engineering The definition of toughness requirements for load‐bearing steel structures for mobile cranes are largely based on empirical values or their derivation is not transparent and understandable. For the first time, fracture mechanical methods enabled the assessment of requirements for material toughness for brittle fracture‐proof operation in a differentiated manner and quantified in a comprehensible manner. The methodology presented, allows the expected service life and the required material toughness to be estimated for various components, load conditions and specifications for weld seam irregularities.